2022
DOI: 10.1002/cbin.11725
|View full text |Cite
|
Sign up to set email alerts
|

The role of mesenchymal stem cells in liver injury

Abstract: Recently, mesenchymal stem cell (MSC) therapy has been suggested as an effective alternative approach for the treatment of hepatic diseases. MSCs have potential therapeutic value, because they have high self-renewal ability, are capable of multipotent differentiation, and have low immunogenicity. Furthermore, MSCs have the potential to differentiate into hepatocytes, and the therapeutic value exists in their immunemodulatory properties and secretion of trophic factors, such as growth factors and cytokines. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 52 publications
0
6
0
Order By: Relevance
“…EMSCs slowly shed from the scaffolds and migrated to the liver parenchyma and proliferated in the area between the scaffolds and liver parenchyma. The local microenvironment of liver injury promoted the differentiation of EMSCs into hepatocyte-like cells [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…EMSCs slowly shed from the scaffolds and migrated to the liver parenchyma and proliferated in the area between the scaffolds and liver parenchyma. The local microenvironment of liver injury promoted the differentiation of EMSCs into hepatocyte-like cells [ 27 ].…”
Section: Resultsmentioning
confidence: 99%
“…19 IL-6 also functions as an anti-apoptotic molecule by increasing the expression of anti-apoptotic factors such as Bcl-2 and Bcl-xl during liver repair. 19,20 SDF-1 or CXCL12, is a cytokine expressed by normal liver cells. Its expression will increase in acute or chronic cell damage.…”
Section: Discussionmentioning
confidence: 99%
“…Mesenchymal stem cells (MSCs), as one of the multipotent cells, have the potential to self-renew and differentiate into multiple types of cells, such as epithelial cells or hepatocytes [ 1 , 2 ]. Studies in animal models have shown that MSC therapy can improve liver function, ameliorate liver fibrosis and reverse acute hepatic failure [ 3 5 ].…”
Section: Introductionmentioning
confidence: 99%